Functional changes of local DMOs in the modern tourism economy - Fedyk, Wojciech; Sołtysik, Mariusz; Bagińska, Justyna; Kołodziej, Małgorzata; Borzyszkowski, Jacek (Bulletin of Geography. Socio-economic Series, 2025)
The objectives of the article are to identify the operational forms and roles of local DMOs (Destination Managment Organization), resulting in an increased organisational effectiveness within a given operational model. The study provides an addition to the extant body of knowledge concerning the relevance and effectiveness of local DMOs’ operating models and their roles. The CAWI survey results of the entirety of 125 local Polish DMOs indicate that their organisational structures have become obsolete. Their reorganisation into network cooperation organisations, clusters or consortiums of tourism products or management organisations in tourist destinations has been shown to have great adaptive potential and will affect their effectiveness. The study has identified key roles for increasing local DMOs’ effectiveness, as well as the functions that should be limited....